2001
DOI: 10.1148/radiographics.21.1.g01ja02161
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal Hodgkin Disease: Spectrum of Disease

Abstract: Extranodal lesions in Hodgkin disease may develop and spread to virtually any organ system, simulating other neoplastic or infectious diseases. It is important to determine whether extranodal involvement represents a primary manifestation or dissemination of systemic disease, which has a poorer prognosis. Computed tomography (CT) is the preferred modality, although ultrasonography and magnetic resonance (MR) imaging may also be helpful. CT is superior to conventional radiography in assessing chest disease, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
197
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(208 citation statements)
references
References 59 publications
5
197
0
6
Order By: Relevance
“…Heart and pericardium are rarely involved in NHL. The involvement is usually revealed by cardiac complications and is associated with a poor prognosis [21,22]. Few cases of cardiac involvement in NHL have been reported, both primary and metastatic, detected by 18 F-FDG PET-CT [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Heart and pericardium are rarely involved in NHL. The involvement is usually revealed by cardiac complications and is associated with a poor prognosis [21,22]. Few cases of cardiac involvement in NHL have been reported, both primary and metastatic, detected by 18 F-FDG PET-CT [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…However, early lymphomatous bone involvement with a normal CT appearance may be depicted by 18 F-FDG PET [5]. Moog and coworkers found 18 F-FDG PET/CT to be more sensitive and specific than 99m Tc-methylene diphosphonate bone scintigraphy for the detection of osseous involvement by lymphoma [6], and many recent studies have concluded that 18 F-FDG PET/CT has a significant role to play at baseline and for the evaluation of treatment response and restaging of malignant lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,13,14 NHLs amounts to the majority of the extranodal lymphomas in the head and neck region. [15][16][17][18] Lymphoid aggregations in the Waldeyer's ring is the commonest site in the head neck region for extranodal lymphomas. [15][16][17][18] Extranodal primary laryngeal NHLs account to less than 1% of the laryngeal neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Lymphoid aggregations in the Waldeyer's ring is the commonest site in the head neck region for extranodal lymphomas. [15][16][17][18] Extranodal primary laryngeal NHLs account to less than 1% of the laryngeal neoplasms. 3 Usually the laryngeal lymphomas are of a high grade and the low grade tumors are usually arising from MALT.…”
Section: Discussionmentioning
confidence: 99%